ANALYSIS ON FATIGUE CRACK INITIATION LIFE OF COUPLER KNUCKLE OF RAILWAY HEAVY-HAUL WAGON - TIAN XiaoChen; ZHU Tao; WANG Chao; YIN MinXuan; XU JingTao; XIAO ShouNe; YANG GuangWu; YANG Bing (Jixie qiangdu)
In order to more accurately grasp the health status of key parts of heavy-haul wagon, the crack initiation life of the structure under existing service conditions is one of the important links of the research. In order to accurately analyze the fatigue crack initiation life of heavy-haul wagon coupler knuckle, an analysis manner of fatigue crack initiation life based on the separated body model is proposed. Firstly, the uniform load model based on strain test points, the contact force model based on contact nonlinearity, and the load distribution model based on load-bearing characteristics were constructed respectively, three types of knuckle crack initiation life models under different load conditions; Then, the finite element simulation under the three load-bearing conditions and bench test results of the knuckle are compared and analyzed, and it is proved that the elastic strain calculation results of each test point in the uniformly distributed load model based on strain test points are in good agreement with the results of bench test; Finally, based on the uniform load model and the local stress-strain method, the fatigue crack initiation life analysis of the heavy-haul wagon coupler knuckle is carried out. It shows that the dangerous part of the knuckle fatigue damage is the roots of the upper and lower traction flanges. Under specific load spectrum conditions, 95% confidence and 90% survival rate, its fatigue crack initiation life is 12 200 kilometers.